Fenomena gerhana matahari dan kesannya - Mat Nor, A.; Haron, S.; Chin, W.L.; Hafiz, M.; Zainuddin, M.Z. (2009)
Eclipse of the sun phenomenon 's impact on environment of earth was done during annular solar eclipse at Pantai Anyer, Banten, Indonesia. Observation result show distinct change detected during maximum annular solar eclipse. The effect of an annular solar eclipse on the enviroment will be discussed in this paper.